A functional study of the role of Turandot genes in Drosophila melanogaster: An emerging candidate mechanism for inducible heat tolerance. (November 2022) - Amstrup, Astrid Bay; Bæk, Ida; Loeschcke, Volker; Givskov Sørensen, Jesper
Graphical abstract: Abstract: Plastic responses to heat stress have been shown to temporarily increase heat stress tolerance in many small ectotherms. Heat shock proteins (Hsps) have previously been shown to play a role in this induced heat stress tolerance. The heat shock response is fast but short lived, with the cellular Hsp concentration peaking within a few hours after induction. Induced heat stress tolerance, on the other hand, peaks 16–32 h after induction. Therefore, the inducible heat stress response must depend on additional mechanisms. The Turandot gene family has been suggested as a candidate. It contains eight genes that are all upregulated to some degree following heat stress in Drosophila melanogaster . Previously, Turandot A ( totA ) and Turandot X ( totX ) have been linked to induced heat stress tolerance. The study presented here aimed to investigate the temporal dynamics of Turandot expression and the functional role of totA and totC for heat stress tolerance. This was done by assaying the temporal heat tolerance and Turandot gene expression after a heat insult, and by exposing Turandot gene knock down flies to a range of heat hardening treatments, and evaluating the effects on heat tolerance. Successful gene knock down was verified by gene expression assays. In addition, expression of hsp70A was included. Both totA, totC, and hsp70A expression increased following a heat hardening treatment, while the results for totX were less clear. The expression of totC temporally co-occurred with and was functionally linked to increased heat tolerance. Expression of totA did not have a significant effect on heat stress tolerance. The complexity of inducible heat tolerance was underlined by the result that knock down of Turandot genes led to increased expression of hsp70 . The results suggest that heat tolerance is determined by the interaction between several mechanisms, of which Turandot genes constitute one such mechanism.